2021
DOI: 10.3389/fphys.2021.691919
|View full text |Cite
|
Sign up to set email alerts
|

Young Swimmers' Anthropometrics, Biomechanics, Energetics, and Efficiency as Underlying Performance Factors: A Systematic Narrative Review

Abstract: Introduction: In youth swimming, researchers are interested in understanding how anthropometry and parameters related to swimming technique (biomechanics, energetics, and efficiency) influence the performance. However, there is not any review in the literature that consolidates the body of knowledge of this topic. The objective of this study was to review systematically the current body of work on the influence of determinant factors related to swimming technique (biomechanics, energetics, and efficiency) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Additionally, high-performing senior females demonstrated significantly higher SI at late junior age compared to their lower-performing peers (very large effect sizes). This finding corresponds with existing literature showing that faster (early junior) swimmers distinguished themselves from others with better SI ( Barbosa et al, 2019 ; Morais et al, 2021 ). However, contrary to our initial hypothesis, no differences in SI were observed among males.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, high-performing senior females demonstrated significantly higher SI at late junior age compared to their lower-performing peers (very large effect sizes). This finding corresponds with existing literature showing that faster (early junior) swimmers distinguished themselves from others with better SI ( Barbosa et al, 2019 ; Morais et al, 2021 ). However, contrary to our initial hypothesis, no differences in SI were observed among males.…”
Section: Discussionsupporting
confidence: 92%
“…However, with most studies in elite swimming focusing on adults ( Costa et al, 2012 ), little is known about the developmental pathway towards swimming expertise. For example, the systematic narrative review of Morais et al (2021) found only eight longitudinal studies on youth swimmers’ development over multiple seasons, highlighting the need for research that shed light on the journey towards swimming excellence.…”
Section: Introductionmentioning
confidence: 99%
“…Swimming velocity is highly dependent from anthropometric variables ( Nevill et al, 2020 ; Oliveira et al, 2021 ), kinematics and motor control ( Morais et al, 2012 ; Figueiredo et al, 2016 ; Silva et al, 2019 ), energetics/efficiency ( Figueiredo et al, 2016 ; Barbosa et al, 2019 ), and dry-land strength and power ( Girold et al, 2012 ; Strzala et al, 2019 ). However, most recent research trends highlighted swimming performance as a holistic phenomenon that is strongly dependent from the interaction between several variables of different scientific fields ( Figueiredo et al, 2016 ; Morais et al, 2021 ). The potential interaction between swimming performance determinants (i.e., scientific fields, domains, and variables that may determine or predict swimming performance) provides the platform for different and multiple patterns of behavior to emerge on an individual basis.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of providing more comprehensive evaluation and optimization of swimming performance, previous research has demonstrated and suggested to consider multiple factors, including, anthropometrics, gender, age, or skill level/experience (Morais et al, 2021b; for comparison and evaluation. Therefore, without sufficient participants' information and variety of study population, this might limit our understanding of certain population and unable to use scientific evidence to support the planning of different trainings.…”
Section: Research Q2: What Kinds Of Participants Were Mostly Be Inves...mentioning
confidence: 99%